Quadriceps Strength following Anterior Cruciate Ligament Reconstruction: Normative Values based on Sex, Graft Type and Meniscal Status at 3, 6 & 9 Months - Nicole A. Schwery; Michael T. Kiely; Christopher M. Larson; Corey A. Wulf; Christie S. Heikes; Ryan W. Hess; M. Russell Giveans; Braidy S. Solie; Chrisopher P. Doney (International Journal of Sports Physical Therapy)
# Background